Expert ratings of job demand and job control as predictors of injury and musculoskeletal disorder risk in a manufacturing cohort. Issue 4 (10th July 2015) - Cantley, Linda F; Tessier-Sherman, Baylah; Slade, Martin D; Galusha, Deron; Cullen, Mark R
Abstract : Objective: To examine associations between workplace injury and musculoskeletal disorder (MSD) risk and expert ratings of job-level psychosocial demand and job control, adjusting for job-level physical demand. Methods: Among a cohort of 9260 aluminium manufacturing workers in jobs for which expert ratings of job-level physical and psychological demand and control were obtained during the 2 years following rating obtainment, multivariate mixed effects models were used to estimate relative risk (RR) of minor injury and minor MSD, serious injury and MSD, minor MSD only and serious MSD only by tertile of demand and control, adjusting for physical demand as well as other recognised risk factors. Results: Compared with workers in jobs rated as having low psychological demand, workers in jobs with high psychological demand had 49% greater risk of serious injury and serious MSD requiring medical treatment, work restrictions or lost work time (RR=1.49; 95% CI 1.10 to 2.01). Workers in jobs rated as having low control displayed increased risk for minor injury and minor MSD (RR=1.45; 95% CI 1.12 to 1.87) compared with those in jobs rated as having high control. Conclusions: Using expert ratings of job-level exposures, this study provides evidence that psychological job demand and job control contribute independently to injury and MSD risk in a blue-collar manufacturing cohort, and emphasises the importance of monitoring psychosocial workplace exposures in addition to physical workplace exposures to promote worker health and safety.